Decision-Making of Swiss Farmers and the Role of the Veterinarian in Reducing Antimicrobial Use on Dairy Farms - Gerber, Manuela; Dürr, Salome; Bodmer, Michèle (Frontiers in Veterinary Science, 2020)
The reduction of antimicrobials on dairy farms is a topical issue and confronts both veterinarians and farmers with major challenges. The aim of this study was to investigate dairy farmers' motivation to reduce antimicrobial use on their farms. Factors influencing dairy farmers' decision-making regarding dairy cow health were identified and the role of the veterinarian in these processes was characterized. A customized structured questionnaire was sent to all participants (n = 59) of an ongoing antimicrobial reduction project among dairy farmers in the Canton of Fribourg, Switzerland, by mail. Fifty-eight completed questionnaires were returned and evaluated (response rate 98.3%). The majority of respondents were men (56/58, 96.6%) and farm managers (55/57, 96.5%) managing their farms as their main occupation (56/57, 98.2%). Using a 5-point-Likert-scale (1 = not a reason, 5 = very important reason), respondents ranked “My veterinarian is putting pressure on us to use less antimicrobials” (median=2.5, interquartile range = 1–3) and “Other farmers also reduce antimicrobial use” (2.0, 1–3) as the least important factors affecting their motivation to reduce the use of antimicrobials in dairy cows (P < 0.001). Respondents ranked their veterinarian's opinion (4.0, 4–5) and their own feelings and knowledge (4.0, 3–4) as the two factors having significantly more importance on their decisions regarding dairy cow management (P < 0.001). The farmers indicated they were satisfied with the quality of the consultancy given by their veterinarians (4.0, 4–5) and with the quality of communication with veterinarians (4.0, 3–4). They indicated that they understood recommendations made by the veterinarian (4.0, 3.75–4) and also felt understood by the veterinarian (4.0, 3–4). However, only 25.9% (14/54) indicated they were willing to pay for good quality, farm-adapted consulting by their veterinarian. Based on these findings, veterinarians play an important role in influencing Swiss dairy farmers in decision-making concerning animal health and treatment. However, veterinarians were not viewed by farmers as important motivators for reducing antimicrobial use. Swiss veterinarians are encouraged to be aware of their influence on farmers' decisions and to use that influence to more clearly promote antimicrobial reduction on dairy farms.